Does Body Mass Index Influence Social Media Use? An Exploration of Social Media Use in College Students (P04-009-19). (13th June 2019) - Haddadian, Padideh; Coccia, Catherine
Abstract: Objectives: To examine the relationship between college dietetic students' body mass index (BMI), body image, social desirability and social media use. Methods: This study is a secondary data analysis. The study population consisted of 42 male and female nutrition and dietetic students at a large southeastern University. The demographics of the students were 70.7% White, 17.1% Black, 9.8% Asian, 2.4% American Indian and 46.3% identified as Hispanic. The sample included 41.4% undergraduate and 58.5% graduate students. Descriptive statistics, analysis of variance (ANOVA) and general linear regression was conducted using SPSSv20. Results: Regression analysis indicated that social desirability (t = −2.23, P  = .03) and BMI category (t = −2.18, P  = .04) were both negatively related to the number of social media platforms students participated in. Body image had no relationship with the number of platforms students engaged with (t = −.301, P  = .765). However, number of hours spent on social media platforms increased as BMI categorization increased [F = 3.654, P  = 0.22]. Conclusions: Student BMI and social desirability were related to the number of social media platforms students engage in and the amount of time they spend posting information online. Future studies are needed to further examine the role body image, BMI and social desirability play in student online behavior. Funding Sources: Private.